The Role of the Provincial Administration in Reorganization of Tambov in the last quarter of the 18th Century - Gryaznova, Nadezhda (project baikal, 2016)
The article describes the process of spatial reorganization of provincial cities in accordance with the ideas expressed in the model of an ideal state formed by Ekaterina II. Town-planning and architectural reorganization of the province is viewed as a component of the ‘cultural charity’ of the provincial authorities or an endeavor to recreate the elements of the metropolitan way of life in the Russian province. The behavioral model demonstrated by the provincial authorities is considered to be a messianic opportunity to give an example to follow. The article deals with the activities of Tambov governors-general and governors R. I. Vorontsov, M. F. Kaminsky, I. V. Gudovich, G. R. Derzhavin etc.